“Spel van misleiding”: Over de kunst van Hafid Bouazza - Louwerse, Henriëtte (Department of Dutch and South African Studies, Faculty of English, 2008)
Hafid Bouazza is an influential and celebrated author in the Netherlands today. In the context of contemporary Dutch literature, Bouazza’s Moroccan background still marks a divergence from the born-and-bred Dutch norm. Bouazza both challenges and uses this position to the full. His writing demonstrates that the perceived us-them or self-other oppositions are questionable ideological constructs. He undermines the concept of a unified culture and the wholeness of the self. He explores and exploits stereotypical beliefs held on both sides of the East/West divide. The result is a magical realist setting that both puzzles and enchants. This contribution offers an overview of Bouazza's main thematic concerns in this literary prose to date.
Keywords: cultural identity; migration; stereotyping; East-West opposition; artistic autonomy